African foreign policies : selecting signifiers to explain agency - Bischoff, Paul, 1954- (New York : Routledge, 2020)
"This book explores, at a time when several powers have become serious players on the continent, aspects of African agency, past and present, by African writers on foreign policy, representative of geography, language and state size. In the past, African foreign policy has largely been considered within the context of reactions to the international or global 'external factor'. This ground-breaking book, however, looks at how foreign policy has been crafted and used in response not just to external, but also, mainly, domestic imperatives or (theoretical) signifiers. As such, it narrates individual and changing foreign policy orientations over time - and as far back as independence - with mainly African-based scholars who present their own constructs of what is a useful theoretical narrative regarding foreign policy on the continent - how theory is adapted to local circumstance or substituted for continentally based ontologies. The book therefore contends that the African experience carries valuable import for expanding general understandings of foreign policy in general. This book will be of key interest to scholars and students of Foreign Policy Analysis, Foreign Policy Studies, African International Relations/Politics/Studies, Diplomacy and more broadly to International Relations"--
Introduction / Paul-Henri Bischoff -- What Next? Past and present African foreign policy concepts and practices / Paul-Henri Bischoff -- The African Union as a Foreign Policy Player: African Agency in International Cooperation / Tshepo Gwatiwa -- Unprincipled Pragmatism and Anti-Imperialist Impulses in an Interconnected World: The Zuma Presidency, 2009-2017 / Mzukisi Qobo -- Towards A Strategic Culture Approach to Understanding and Conceptualising Ethiopia's Foreign Policy Towards Israel and the Middle Eastern Arab Countries / Makonnen Tesfaye -- Nigeria's Foreign Policy and Intervention Behaviour in Africa: What Role for Agency? / Olumuyiwa Amao -- Zimbabwe and New Signifiers: Towards a cultural political economy of Foreign Policy Making / Mike Mavura -- Realist Conceptions of Kenya's Foreign Policy and Foreign Policy Behaviour: A Theoretical and Contextual Disposition / Korwa Gombe Adar and Mercy Kathambi Kaburu -- Addressing the Conceptual Void of African Small State Foreign Policy in Orthodox Theory: A Case Study of Botswana's Principled Pragmatism / Kabelo M. Mahupela -- Tunisia's Foreign Policy Towards France Before and After an Undemanding 'Revolution': A Theoretical Explanation of the An-Nahdha-led Interim Governments' Soft Policy / Ahmed Ali Salem -- Straddling Between Convergence and Divergence: A Constructivist's View of Malawi's Foreign Policy in Post-independence Africa / Eugenio Njoloma -- Strategies of a Small State Between Realism and Liberalism: Sixty Years of Guinea's Diplomacy and Foreign Policy (1958-2018) / Issaka K. Souaré -- Rethinking SADC's Collective Policymaking Processes on External Relations and Non-state Participation for Region-building / Cecilia Lwiindi Nedziwe -- Towards an Understanding of the Interplay Between Ghana's Foreign and Defence Policies / Kwesi Aning and Kwaku Danso -- Conclusion / Paul-Henri Bischoff.
OCLC-licensed vendor bibliographic record.
Keywords: Africa -- Foreign relations -- 1960-; Africa -- Politics and government -- 1960-; POLITICAL SCIENCE / International Relations / General